2021
DOI: 10.1073/pnas.2014605118
|View full text |Cite
|
Sign up to set email alerts
|

The KRAS and other prenylated polybasic domain membrane anchors recognize phosphatidylserine acyl chain structure

Abstract: KRAS interacts with the inner leaflet of the plasma membrane (PM) using a hybrid anchor that comprises a lysine-rich polybasic domain (PBD) and a C-terminal farnesyl chain. Electrostatic interactions have been envisaged as the primary determinant of interactions between KRAS and membranes. Here, we integrated molecular dynamics (MD) simulations and superresolution spatial analysis in mammalian cells and systematically compared four equally charged KRAS anchors: the wild-type farnesyl hexa-lysine and engineered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
112
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(138 citation statements)
references
References 53 publications
10
112
0
Order By: Relevance
“…As the sample Ripley's K-function curve in Figure 2C illustrates, peak clustering of GFP-RAS occurs at the radial length r of ∼20 nm, suggesting that the most probable radius of GFP-RAS nanoclusters is approximately 20 nm Plowman et al, 2005;Zhou et al, 2014;Liang and et al, 2019;Zhou et al, 2021). The K-function analysis further showed that RAS nanoclusters contain approximately 6-7 RAS molecules, and suggests that nearly half of GFP-RAS molecules exist as monomers, ∼30% as dimers, >10% as trimers, and <10% of GFP-RAS form higher order multimers .…”
Section: Isoform-specific Nanoclustering Of Rasmentioning
confidence: 99%
See 4 more Smart Citations
“…As the sample Ripley's K-function curve in Figure 2C illustrates, peak clustering of GFP-RAS occurs at the radial length r of ∼20 nm, suggesting that the most probable radius of GFP-RAS nanoclusters is approximately 20 nm Plowman et al, 2005;Zhou et al, 2014;Liang and et al, 2019;Zhou et al, 2021). The K-function analysis further showed that RAS nanoclusters contain approximately 6-7 RAS molecules, and suggests that nearly half of GFP-RAS molecules exist as monomers, ∼30% as dimers, >10% as trimers, and <10% of GFP-RAS form higher order multimers .…”
Section: Isoform-specific Nanoclustering Of Rasmentioning
confidence: 99%
“…The enrichment of specific lipids within different RAS nanoclusters has been investigated using EM-bivariate coclustering analysis of GFP-tagged lipid-binding domains that bind specific lipids (some examples listed in Figure 2H) and RFP-tagged RAS proteins on intact PM sheets (Zhou et al, 2014;Liang et al, 2019;Zhou et al, 2021). These experiments were complemented by FLIM-FRET in live cells expressing RFP-tagged RAS isoforms and spike-labeled TopFluor-tagged fluorescent lipids exogenously supplemented to these cells (Zhou et al, 2014;Liang et al, 2019;Zhou et al, 2021). The EM co-clustering analysis showed that RFP-KRAS4BG12V co-localized extensively with the PS probe GFP-LactC2 and the PA probe GFP-PASS, but not with the PIP 2 probe GFP-PH-PLCδ, the PIP 3 probe GFP-PH-Akt or the cholesterol probe GFP-D4H (Zhou et al, 2014;.…”
Section: Ras Nanoclusters Sort Lipids In a Headgroup-and Acyl Chain Structure-specific Mannermentioning
confidence: 99%
See 3 more Smart Citations